Perspektif Al-Ghazali tentang Maslahah dan Profit dalam Konteks Produksi Modern - Nur Rahmi Zuhra; Nurhayati; Yenni Samri Juliati Nasution (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study examines Al-Ghazali's thoughts on the concepts of production, profit, and maslahah in Islamic economic ethics and their relevance to modern production practices that tend to be profit-oriented and industrialized. This study uses a qualitative approach based on library research by examining Al-Ghazali's primary works such as Ihya' Ulumuddin, Al-Mustashfa, and Mizan al-Amal as well as secondary sources in the form of Islamic economic journals and literature. The results show that Al-Ghazali places maslahah as the main principle in production activities, while profit is considered legitimate as long as it does not cause injustice or social and environmental damage. This thinking is relevant to addressing contemporary production challenges, especially in terms of sustainable ethics, worker welfare, and moral responsibility. This study contributes by offering a maslahah-based ethical framework to assess and direct modern production practices to be more just and oriented towards the welfare of the community.